2013
DOI: 10.1186/1471-2458-13-508
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of knowledge, attitude and practice towards post exposure prophylaxis for HIV among health care workers in Gondar, North West Ethiopia

Abstract: BackgroundHIV/AIDS infection in health care facility has become a major health problem. Especially in resource poor setting health care workers are managing huge number of HIV infected patients that made them to be more exposed to HIV infection. This situation makes the use of post exposure prophylaxis for HIV very important. Therefore the aim of the study was to assess knowledge, attitude and practice of health care workers towards post exposure prophylaxis for HIV.MethodsCross-sectional study was conducted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
91
22

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(131 citation statements)
references
References 6 publications
(6 reference statements)
18
91
22
Order By: Relevance
“…In a study done by Mathewos et al in North West Ethiopia, it was found that the percentage of exposed respondents who took PEP (74.2%) was lower than the present study (88.2 %). 17 Many studies on PEP for HIV have shown that the rate of completion of prescribed PEP regimen ranges from 60-94%. [17][18][19] This particular parameter was not considered in our study which happens to be the limitation of the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study done by Mathewos et al in North West Ethiopia, it was found that the percentage of exposed respondents who took PEP (74.2%) was lower than the present study (88.2 %). 17 Many studies on PEP for HIV have shown that the rate of completion of prescribed PEP regimen ranges from 60-94%. [17][18][19] This particular parameter was not considered in our study which happens to be the limitation of the study.…”
Section: Discussionmentioning
confidence: 99%
“…17 Many studies on PEP for HIV have shown that the rate of completion of prescribed PEP regimen ranges from 60-94%. [17][18][19] This particular parameter was not considered in our study which happens to be the limitation of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, 61/83 (73.5%) and 57/83 (68.67%) did not take any antiretroviral (ARV) PEP for HIV and did not report their injury to their supervisor for immediate medical attention (Table II and III) despite there is ARV PEP and line of reporting system with assigned supervisor. 13,14 All these figures showed that infection prevention activities were neglected in Bahir Dar city administrative healthcare facilities. The healthcare workforce, 35 million people world wide, represents 12% of the working population.…”
Section: Discussionmentioning
confidence: 99%
“…4 Whilst most studies on the efficacy of PEP are derived from animal models, retrospective data from prevention of mother-to-child transmission (PMTCT) studies and occupational exposure support the efficacy in human subjects and also among health care providers in Europe and the U.S. 1,5,6 Health care providers are at risk of occupational HIV acquisition worldwide with 3/1000 injuries resulting in HIV transmission after percutaneous exposure from an HIV infected patient in health settings. [7][8][9] Several studies have explored knowledge on PEP for HIV among healthcare providers as a whole, nurses, medical doctors, surgical residents, midwifery students, medical interns and dental students.…”
Section: Introductionmentioning
confidence: 99%
“…They are frequently exposed to occupational hazards through percutaneous injury such as needle stick or cut with sharps, contact with the mucus membrane of eyes or mouth of an infected person, contact with non-intact skin exposed with blood, or other potentially infectious body fluids. 23 The medical, nursing and paramedical students are usually extremely busy and overburdened in a busy and tertiary care hospital. Thus, personal protection may not always remain a priority for them and they may also have constraints of resources for prevention of occupational exposures, such as hand gloves.…”
Section: Introductionmentioning
confidence: 99%